Anode active material, its preparation method, and anode pieces, electrochemical devices, and electronic devices containing the same
By using hard carbon materials containing carbon, hydrogen, nitrogen and transition metal elements in the negative electrode living of the battery, the problem of difficult to take into account the energy density, charge and discharge characteristics and safety performance in the prior art is solved, and the effects of high energy density and fast charge and discharge are achieved.
Patent Information
- Application Number
- JP2024556769
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-03-28
- Publication Date
- 2025-04-14
- Estimated Expiration
- 2042-03-28
AI Technical Summary
The prior art is difficult to achieve both high energy density, fast charging and discharging characteristics and safety performance in the battery field.
A hard carbon material containing carbon, hydrogen, nitrogen and transition metal elements is used as the negative electrode living substance. Through reasonable element composition and distribution, the electronic conductivity and charge and discharge performance of the material are improved.
It achieves high reversible gramm capacity, good electronic conductivity and fast charging and discharging characteristics, improving the overall performance of the battery.
Smart Images

Figure 2025510261000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and more specifically, to a negative electrode active material, a method for preparing the same, and a negative electrode sheet, an electrochemical device, and an electronic device including the same.
Background Art
[0002] Secondary batteries have advantages such as high energy density, high operating voltage, long cycle life, small volume, light weight, and environmental friendliness, and are currently widely applied in fields such as electric vehicles and mobile electronic devices. With the development of electric vehicles and mobile electronic devices, the requirements for the energy density, cycle characteristics, rapid charge and discharge characteristics, safety performance, etc. of secondary batteries are increasing. Therefore, providing a secondary battery with comprehensively improved overall characteristics is a technical problem that needs to be urgently solved at present.
Summary of the Invention
[0003] An object of the present invention is to provide a negative electrode active material, a method for preparing the same, and a negative electrode sheet, an electrochemical device, and an electronic device including the same, and the negative electrode active material can have a high capacity per reversible gram, good electronic conductivity, and rapid charge and discharge characteristics.
[0004] A first aspect of the present invention provides a negative electrode active material including a hard carbon material, the hard carbon material includes a carbon element, a hydrogen element, a nitrogen element, and a transition metal element, and when the mass percentage of the carbon element is A%, the mass percentage of the hydrogen element is B%, the mass percentage of the nitrogen element is C%, and the mass percentage of the transition metal element is D% with respect to the total mass of the hard carbon material, A and B satisfy 0.003 ≦ B / A ≦ 0.050, C satisfies 0 < C ≦ 12.0, and D satisfies 0 < D ≦ 5.0.
[0005] In the course of research, the inventors of the present invention have found that by simultaneously doping a hard carbon material with an appropriate amount of nitrogen element and transition metal element, the negative electrode active material can have both a high reversible capacity per gram, good electronic conductivity, and rapid charge / discharge characteristics.
[0006] In some embodiments, the X-ray photoelectron spectrum of the negative electrode active material includes three different N peaks, namely, pyrrole nitrogen, pyridine nitrogen, and graphitized nitrogen. The sum of the peak area corresponding to pyrrole nitrogen and the peak area corresponding to pyridine nitrogen is X, and the peak area corresponding to graphitized nitrogen is Y, where X and Y satisfy 0.6≦X / Y≦1.4. Optionally, X and Y satisfy 0.7≦X / Y≦1.3. In this case, the negative electrode active material can contain a relatively large amount of pyrrole nitrogen and pyridine nitrogen, so that there are many defects on the graphite crystallite end face, which can fully exert the effect of reducing the band gap energy by nitrogen atoms, and further, the hard carbon material of the present invention can have good electronic conductivity and rapid charge / discharge characteristics.
[0007] In some embodiments, A satisfies 65≦A≦96. Optionally, A satisfies 70≦A≦94.
[0008] In some embodiments, B satisfies 0.3≦B≦4.0. Optionally, B satisfies 1.0≦B≦2.5.
[0009] In some embodiments, C satisfies 0.1≦C≦12.0. Optionally, C satisfies 5.0≦C≦12.0. When the nitrogen content is in an appropriate range, the electronic conductivity and rapid charge / discharge characteristics of the hard carbon material can be further improved, and the plateau voltage at high potential of the hard carbon material can be further reduced, thereby further increasing the output voltage and energy density of the entire electrochemical device.
[0010] In some embodiments, D satisfies 0.2≦D≦5.0. Optionally, D satisfies 0.2≦D≦1.2. When the content of the transition metal element is in an appropriate range, the electronic conductivity and rapid charge / discharge characteristics of the hard carbon material can be further improved, and the plateau voltage at high potential of the hard carbon material can be further reduced, thereby further increasing the output voltage and energy density of the entire electrochemical device.
[0011] In some embodiments, A and B satisfy 0.004≦B / A≦0.035. Optionally, A and B satisfy 0.007≦B / A≦0.030.
[0012] In some embodiments, C and D satisfy 3.0≦C / D≦18. Optionally, C and D satisfy 6.5≦C / D≦18. When the content ratio of nitrogen element to transition metal element is within an appropriate range, the hard carbon material can better combine high reversible capacity per gram with good electronic conductivity and rapid charge / discharge properties.
[0013] In some embodiments, the transition metal element comprises at least one of Mn, Co, Ni, Cu, Zn, Sc, Ti, V, Cr, Fe, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, W, Pt, and Au. Optionally, the transition metal element comprises at least one of Mn, Co, Ni, Cu, and Zn.
[0014] In some embodiments, the nitrogen element and the transition metal element are uniformly distributed in the hard carbon material.
[0015] In some embodiments, when an average content of nitrogen element in any 500 nm × 500 nm area on the surface of the hard carbon material is M1, and an average content of nitrogen element in any 500 nm × 500 nm area inside the hard carbon material is M2, M1 and M2 satisfy 0.9 ≦ M2 / M1 ≦ 1.1.
[0016] In some embodiments, when an average content of transition metal elements in any 500 nm × 500 nm area on the surface of the hard carbon material is M3, and an average content of transition metal elements in any 500 nm × 500 nm area inside the hard carbon material is M4, M3 and M4 satisfy 0.9≦M4 / M3≦1.1.
[0017] In some embodiments, the anode active material further comprises a conductive carbon shell layer located on the surface of the hard carbon material. Optionally, the conductive carbon shell layer comprises at least one of amorphous carbon, graphene, carbon nanotubes, and vapor-grown carbon. Coating the surface of the hard carbon material with a conductive carbon shell layer can improve the interface stability of the anode active material, thereby improving the initial coulombic efficiency of the anode active material. Coating the surface of the hard carbon material with a conductive carbon shell layer can also increase the storage sites of the anode active material, so that the anode active material can have a higher reversible capacity per gram.
[0018] In some embodiments, the negative electrode active material has a volume particle size Dv50 of 3 μm to 15 μm.
[0019] In some embodiments, the negative electrode active material has a volume particle size Dv99 of 10 μm to 45 μm.
[0020] In some embodiments, the transition metal particles in the negative electrode active material have a volume particle size Dv50 of 10 nm to 100 nm. In some embodiments, the negative electrode active material has an initial reversible capacity per gram at 0 V to 2.0 V of 300 mAh / g to 1000 mAh / g.
[0021] The second aspect of the present invention provides a method for preparing a negative electrode active material, and the preparation method includes the following steps S10, step S20, step S30, and step S40. Step S10: Provide a hard carbon precursor, a nitrogen source, and a transition metal source. Step S20: Uniformly mix the hard carbon precursor, the nitrogen source, and the transition metal source to obtain an initial raw material. Step S30: Pre-oxidize the initial raw material obtained in S20 at a first temperature T1 to obtain a first intermediate product, where T1 satisfies T1≤300°C. Step S40: Perform a primary sintering treatment on the first intermediate product obtained in S30 at a second temperature T2 to obtain a hard carbon material, where T2 satisfies 600°C≤T2≤1000°C. Here, the hard carbon material contains a carbon element, a hydrogen element, a nitrogen element, and a transition metal element. When the mass percentage of the carbon element is A%, the mass percentage of the hydrogen element is B%, the mass percentage of the nitrogen element is C%, and the mass percentage of the transition metal element is D% with respect to the total mass of the hard carbon material, A and B satisfy 0.003≤B / A≤0.050, C satisfies 0<C≤12.0, and D satisfies 0<D≤5.0.
[0022] In some embodiments, the atmosphere of the pre-oxidation treatment is a slightly oxidizing atmosphere.
[0023] In some embodiments, T1 satisfies 140°C≤T1≤300°C.
[0024] In some embodiments, the time of the pre-oxidation treatment is 2h to 48h.
[0025] In some embodiments, the atmosphere of the primary sintering treatment is an inert atmosphere.
[0026] In some embodiments, T2 satisfies 700°C≤T2≤1000°C.
[0027] In some embodiments, the time of the primary sintering treatment is 1h to 10h.
[0028] In some embodiments, the hard carbon precursor comprises at least one of a polymer, a pitch, and a biomass material.
[0029] In some embodiments, the nitrogen source comprises organic amines containing 1 to 20 carbon atoms and salts thereof.
[0030] In some embodiments, the transition metal source comprises at least one of an oxide, a halide, a hydroxide, a sulfate, a carbonate, an oxalate, a nitrate, and an acetate of a transition metal element.
[0031] In some embodiments, the preparation method further includes the following step S50: Step S50: The hard carbon material obtained in S40 is uniformly mixed with the conductive carbon precursor, and then subjected to a secondary sintering treatment at a third temperature T3 to obtain a hard carbon material having a conductive carbon shell layer on the surface, where T3 satisfies T3≦1000° C.
[0032] In some embodiments, the atmosphere for the secondary sintering process is an inert atmosphere.
[0033] In some embodiments, T3 satisfies 700°C≦T3≦1000°C.
[0034] In some embodiments, the time for the secondary sintering treatment is 1 h to 10 h.
[0035] In some embodiments, the conductive carbon precursor comprises at least one of graphene, carbon nanotubes, vapor grown carbon fibers, acetylene, polymers, and pitch.
[0036] A third aspect of the present invention provides an anode piece, the anode piece comprising an anode current collector and an anode film layer, the anode film layer comprising the anode active material of the first aspect of the present invention or the anode active material obtained by the preparation method of the second aspect of the present invention.
[0037] A fourth aspect of the present invention provides an electrochemical device comprising a negative electrode piece according to the third aspect of the present invention.
[0038] A fifth aspect of the invention provides an electronic device comprising an electrochemical device according to the fourth aspect of the invention.
[0039] Since the negative electrode active material of the present invention contains appropriate amounts of nitrogen element and transition metal element, the negative electrode active material of the present invention can combine a high reversible capacity per gram with good electronic conductivity and rapid charge / discharge characteristics, and further, electrochemical devices and electronic devices using the negative electrode active material have improved rapid charge / discharge characteristics and cycle characteristics, as well as high output voltage and energy density. [Brief description of the drawings]
[0040] [Figure 1] FIG. 1 shows the results of XPS fitting of the N peak in the negative electrode active material of Example 14. [Diagram 2] FIG. 2 shows the contents of nitrogen in pyrrole, nitrogen in pyridine, and nitrogen in graphitization in the negative electrode active material of Example 14. [Diagram 3] FIG. 3 shows the dQ / dV-V curves of the negative electrode pieces, where curve I shows Comparative Example 8, curve II shows Comparative Example 2, curve III shows Example 14, and curve IV shows Example 16. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0041] In order to make the objectives, technical solutions and advantages of the present invention clearer, the following will describe the technical solutions of the present invention in detail with reference to the embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, and are not all of the embodiments. The relevant embodiments described in the present invention are for illustration and are used to fundamentally understand the present invention. The embodiments of the present invention should not be construed as limiting the present invention. Based on the technical solutions and embodiments provided by the present invention, all other embodiments obtained by those skilled in the art without creative labor also belong to the scope of the protection claims of the present invention.
[0042] For the sake of brevity, only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unspecified range, and any lower limit can be combined with any other lower limit to form an unspecified range, and likewise any upper limit can be combined with any other upper limit to form an unspecified range. Also, each point or numerical value disclosed alone can be combined with any other point or numerical value, or with any other lower limit or upper limit, to form an unspecified range.
[0043] In the description of this specification, unless otherwise specified, the terms "greater than or equal to" and "less than or equal to" include the numerical value itself.
[0044] Unless otherwise specified, the terms used in the present invention have the meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of each parameter mentioned in the present invention can be measured by various measuring methods commonly used in the art (for example, the measurements can be performed according to the methods shown in the examples of the present invention).
[0045] The term "about" is used to describe and illustrate small variations. When used in conjunction with an event or circumstance, the term can refer to instances where the event or circumstance occurs exactly, and instances where the event or circumstance occurs very similarly. For example, when used in conjunction with a numerical value, the term can refer to a variation range of ±10% or less of the numerical value, such as ±5% or less, ±4% or less, ±3% or less, ±2% or less, ±1% or less, ±0.5% or less, ±0.1% or less, or ±0.05% or less. In this specification, amounts, ratios, and other numerical values may be presented in a range format. Such range formats are for convenience and brevity, and should be interpreted flexibly, and the range formats include not only the numerical values expressly specified as range limits, but also include each and every numerical value or subrange contained in the range, which is equivalent to each numerical value or subrange being expressly specified.
[0046] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terminology means any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means A only, B only, or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means A only, or B only, C only, A and B (excluding C), A and C (excluding B), B and C (excluding A), or all of A, B, and C. Item A may include one component or multiple components. Item B may include one component or multiple components. Item C may include one component or multiple components.
[0047] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form new technical solutions, and such technical solutions should be considered to be included in the disclosure content of the present application.
[0048] Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution, and such technical solution should be considered to be included in the disclosure content of the present application. In this specification, the term "active ions" refers to ions that shuttle between the positive and negative electrodes of an electrochemical device and are absorbed and released, and includes, but is not limited to, lithium ions, sodium ions, and the like.
[0049] With the application and popularity of secondary batteries, their energy density, cycle characteristics, and rapid charge and discharge characteristics have attracted more and more attention. The characteristics of the negative electrode active material determine the characteristics of secondary batteries to a certain extent. Graphite is currently the most commonly used negative electrode active material, and has the advantages of small polarization and stable charge and discharge plateaus. However, the characteristics of commercial graphite are currently almost fully developed, and there is very limited room for improvement in its reversible capacity per gram and energy density. Hard carbon is one of the potential negative electrode active materials to replace graphite, and has the advantage of high reversible capacity per gram, which can well improve the energy density of secondary batteries.
[0050] Hard carbon, by definition, is carbon that is difficult to graphitize, even at high temperatures of 2500°C or higher. Hard carbon is usually obtained using a precursor such as a pyrolytic polymer, and during pyrolysis, the structure in which carbon atoms in the precursor are cross-linked with each other inhibits the growth of the carbon layer in the planar direction, so that the hard carbon structure contains many disordered microcrystals (abbreviated as graphite microcrystals) that resemble the graphite structure. Furthermore, hard carbon has many pores and defect structures, which facilitate the escape and occlusion of ions.
[0051] However, in the course of research, the inventors of the present invention have found that the preparation and use of hard carbon as the negative electrode active material has some drawbacks. For example, hard carbon is quite sensitive to sintering temperature, and when the sintering temperature is high, the capacity per gram of hard carbon is rapidly reduced, while when the sintering temperature is low, the degree of pyrolysis of the precursor is not high enough, which results in a high hydrogen element content in the obtained hard carbon structure, and further worsens the electronic conductivity and rapid charge / discharge properties of hard carbon.
[0052] Also, the dQ / dV-V curve of hard carbon during charging (the vertical axis is the derivative of the capacity per gram with respect to voltage, and the horizontal axis is voltage) usually has two oxidation peaks (corresponding to the two voltage plateaus of the voltage-capacity per gram curve). The plateau voltage at high potential generally exceeds 0.8V, and the plateau voltage at low potential is generally less than 0.2V. For low-temperature type hard carbon obtained by a low-temperature (usually 1000°C or lower) sintering process, since its plateau voltage at high potential is generally high, the output voltage of the entire battery becomes low, and furthermore, the energy density of the battery becomes low. Moreover, for low-temperature type hard carbon obtained by a low-temperature (usually 1000°C or lower) sintering process, its plateau capacity at high potential is high, its plateau capacity at low potential is low, and the irreversible capacity of the corresponding hard carbon is also high, so the energy density of the battery becomes even lower.
[0053] As a result of numerous studies and practices by the inventors of the present invention, a new negative electrode active material that can兼备 a high reversible capacity per gram, good electronic conductivity, and rapid charge and discharge characteristics has been proposed. negative electrode active material
[0054] The first aspect of the embodiment of the present invention provides a negative electrode active material containing a hard carbon material. The hard carbon material contains a carbon element, a hydrogen element, a nitrogen element, and a transition metal element. When the mass percentage of the carbon element is A%, the mass percentage of the hydrogen element is B%, the mass percentage of the nitrogen element is C%, and the mass percentage of the transition metal element is D% with respect to the total mass of the hard carbon material, A and B satisfy 0.003 ≦ B / A ≦ 0.050, C satisfies 0 < C ≦ 12.0, and D satisfies 0 < D ≦ 5.0.
[0055] The hard carbon material of the present invention may be a low-temperature hard carbon material, i.e., a hard carbon material obtained by using a sintering temperature of 1000°C or less, but the hydrogen element content is usually high, and the mass ratio of hydrogen element to carbon element is usually 0.003 to 0.050, and furthermore, the electronic conductivity and rapid charge / discharge characteristics of the hard carbon material are deteriorated. In the course of research, the inventor of the present invention found that by simultaneously doping the hard carbon material with an appropriate amount of nitrogen element and transition metal element, the negative electrode active material can have both a high reversible capacity per gram, good electronic conductivity, and rapid charge / discharge characteristics.
[0056] Without being bound by any theory, the inventors of the present application speculate that the reasons are as follows. First, an appropriate amount of nitrogen element and transition metal element contributes to improving the elemental composition of the defect sites and the edge parts (i.e., end faces) of the graphite microcrystals of the hard carbon material. When nitrogen element is present on the end faces of the graphite microcrystals, it can exist as a nitrogen heterocycle (e.g., pyrrole, pyridine, etc.), and the nitrogen atom can act as an electron carrier to reduce the band gap energy, and further change the electronic structure of the entire hard carbon material, thereby improving its electronic conductivity and rapid charge and discharge properties.
[0057] Secondly, since transition metal elements are good carriers of electrons, doping a hard carbon material with an appropriate amount of transition metal elements can improve its electronic conductivity and rapid charge / discharge properties.
[0058] Thirdly, the appropriate amounts of nitrogen and transition metal elements contribute to increasing the adsorption and desorption ability of active ions at the defect sites and the end faces of graphite crystallites of the hard carbon material, thereby reducing the plateau voltage of the hard carbon material at high potential and reducing the irreversible capacity of the hard carbon material at low potential, and further increasing the output voltage and energy density of the entire electrochemical device.
[0059] Fourth, the appropriate amounts of nitrogen and transition metal elements also contribute to adjusting the location and form of hydrogen in a hard carbon material obtained by a comparable sintering process, thereby further improving the plateau capacity at high potential of the hard carbon material.
[0060] In some embodiments, X-ray photoelectron spectroscopy (XPS) of the negative electrode active material includes three different N peaks, namely, pyrrole nitrogen, pyridine nitrogen, and graphitized nitrogen. When the sum of the peak area corresponding to pyrrole nitrogen and the peak area corresponding to pyridine nitrogen is X and the peak area corresponding to graphitized nitrogen is Y, X and Y satisfy 0.6≦X / Y≦1.4.
[0061] In the negative electrode active material doped with an appropriate amount of nitrogen element, the nitrogen element mainly includes three different forms, namely pyrrolic nitrogen, pyridine nitrogen, and graphitized nitrogen. The nitrogen atom in graphitized nitrogen is obtained by replacing sp2 carbon in the graphite microcrystal, and the graphite microcrystal body structure is hardly changed. The pyrrolic nitrogen and pyridine nitrogen usually have an incomplete 5-membered or 6-membered ring structure, and are usually only present at the graphite microcrystal edge position. Therefore, X / Y can reflect to some extent the defect degree and element composition of the graphite microcrystal edge of the hard carbon material.
[0062] In the anode active material of the present invention, X and Y satisfy 0.6≦X / Y≦1.4, so that the anode active material of the present invention can contain a lot of pyrrole nitrogen and pyridine nitrogen, so that the defects of the graphite microcrystal end face are increased, in this case, the band gap energy reduction effect of nitrogen atoms can be fully exerted, and the hard carbon material of the present invention can have good electronic conductivity and rapid charge and discharge characteristics. And when the graphite microcrystal end face contains a lot of pyrrole nitrogen and pyridine nitrogen, the CH bond content at this site is relatively reduced, so that the position and form of hydrogen element in the hard carbon material are changed, and the plateau voltage at high potential of the hard carbon material is reduced, and finally the output voltage and energy density of the entire electrochemical device can be improved.
[0063] In some embodiments, X / Y is about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.1, about 1.2, about 1.3, or about 1.4, or within a range consisting of any two of these values. Optionally, X and Y satisfy 0.6≦X / Y≦1.3, 0.6≦X / Y≦1.2, 0.6≦X / Y≦1.1, 0.6≦X / Y≦1.0, 0.6≦X / Y≦0.9, 0.7≦X / Y≦1.4, 0.7≦X / Y≦1.3, 0.7≦X / Y≦1.2, 0.7≦X / Y≦1.1, 0.7≦X / Y≦1.0, or 0.7≦X / Y≦0.9.
[0064] In the present invention, the peak areas corresponding to pyrrole nitrogen, pyridine nitrogen, and graphitized nitrogen are calculated from the fitting areas of the corresponding N peaks in X-ray photoelectron spectroscopy (XPS). For example, the fine spectrum of the N peak obtained by XPS measurement is fitted using XPS PEAK analysis software, and it is defined that pyrrole nitrogen is located at 399.6±0.3 eV, pyridine nitrogen is located at 398.5±0.3 eV, and graphitized nitrogen is located at 400.9±0.3 eV, and then the fitting areas of the different N peaks can be obtained using XPS PEAK analysis software.
[0065] In some embodiments, B / A is about 0.003, about 0.004, about 0.005, about 0.006, about 0.007, about 0.008, about 0.009, about 0.010, about 0.012, about 0.014, about 0.016, about 0.018, about 0.021, about 0.024, about 0.027, about 0.030, about 0.035, about 0.040, about 0.045, or about 0.050, or within a range consisting of any two of these values. Optionally, A and B are within the range of 0.004≦B / A≦0.050, 0.004≦B / A≦0.040, 0.004≦B / A≦0.035, 0.004≦B / A≦0.030, 0.004≦B / A≦0.027, 0.005≦B / A≦0.050, 0.005≦B / A≦0.040, 0.005≦B / A≦0.035, 0.005≦B / A≦0.030, 0.005≦B / A≦0.027 , 0.007≦B / A≦0.050, 0.007≦B / A≦0.040, 0.007≦B / A≦0.035, 0.007≦B / A≦0.030, 0.007≦B / A≦0.027, 0.010≦B / A≦0.050, 0.010≦B / A≦0.040, 0.010≦B / A≦0.035, 0.010≦B / A≦0.030, or 0.010≦B / A≦0.027.
[0066] In some embodiments, A satisfies 65≦A≦96. For example, A is about 65, about 68, about 72, about 74, about 76, about 78, about 80, about 82, about 84, about 86, about 88, about 90, about 92, about 94, or about 96, or within a range consisting of any two of these values. Optionally, A satisfies 70≦A≦94, 72≦A≦92, 72≦A≦90, 72≦A≦88, 72≦A≦86, 74≦A≦94, 74≦A≦92, 74≦A≦90, 74≦A≦88, 74≦A≦86, 76≦A≦94, 76≦A≦92, 76≦A≦90, 76≦A≦88, 76≦A≦86, 78≦A≦94, 78≦A≦92, 78≦A≦90, 78≦A≦88, or 78≦A≦86.
[0067] In some embodiments, B satisfies 0.3≦B≦4.0. For example, B is about 0.4, about 0.6, about 0.8, about 1.0, about 1.2, about 1.4, about 1.6, about 1.8, about 2.0, about 2.5, about 3.0, about 3.5, or about 4.0, or within a range consisting of any two of these values. Optionally, B satisfies 0.6≦B≦4.0, 0.6≦B≦3.5, 0.6≦B≦3.0, 0.6≦B≦2.5, 0.6≦B≦2.0, 0.8≦B≦4.0, 0.8≦B≦3.5, 0.8≦B≦3.0, 0.8≦B≦2.5, 0.8≦B≦2.0, 1.0≦B≦4.0, 1.0≦B≦3.5, 1.0≦B≦3.0, 1.0≦B≦2.5, or 1.0≦B≦2.0.
[0068] When the content of nitrogen element is in an appropriate range, the electronic conductivity and rapid charge / discharge characteristics of the hard carbon material can be further improved, and the plateau voltage at high potential of the hard carbon material can be further reduced, thereby further increasing the output voltage and energy density of the entire electrochemical device. In some embodiments, C satisfies 0.1≦C≦12.0. For example, C is about 0.2, about 0.5, about 1.0, about 1.5, about 2.0, about 2.5, about 3.0, about 3.5, about 4.0, about 4.5, about 5.0, about 5.5, about 6.0, about 6.5, about 7.0, about 7.5, about 8.0, about 8.5, about 9.0, about 9.5, about 10.0, about 10.5, about 11.0, about 11.5, or about 12.0, or is within a range consisting of any two of these values. Optionally, C is 2.0≦C≦12.0, 3.0≦C≦12.0, 3.5≦C≦12.0, 4.0≦C≦12.0, 4.5≦C≦12.0, 5.0≦C≦12.0, 5.5≦C≦12.0, 6.0≦C≦12.0, 6.5≦C≦12.0, 7.0≦C≦12.0, 7.5≦C≦12.0, Satisfies 2.0≦C≦10.5, 3.0≦C≦10.5, 3.5≦C≦10.5, 4.0≦C≦10.5, 4.5≦C≦10.5, 5.0≦C≦10.5, 5.5≦C≦10.5, 6.0≦C≦10.5, 6.5≦C≦10.5, 7.0≦C≦10.5, or 7.5≦C≦10.5.
[0069] When the content of the transition metal element is in an appropriate range, the electronic conductivity and rapid charge / discharge characteristics of the hard carbon material can be further improved, and the plateau voltage at high potential of the hard carbon material can be further reduced, thereby further increasing the output voltage and energy density of the entire electrochemical device. In some embodiments, D satisfies 0.2≦D≦5.0. For example, D is about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1.0, about 1.2, about 1.5, about 2.0, about 2.5, about 3.0, about 3.5, about 4.0, about 4.5, or about 5.0, or is within a range consisting of any two of these values. Optionally, D satisfies 0.2≦D≦4.0, 0.2≦D≦3.0, 0.2≦D≦2.0, 0.2≦D≦1.5, 0.2≦D≦1.2, 0.2≦D≦0.8, 0.2≦D≦0.6, 0.3≦D≦4.0, 0.3≦D≦3.0, 0.3≦D≦2.0, 0.3≦D≦1.5, 0.3≦D≦1.2, 0.3≦D≦0.8, 0.3≦D≦0.6, 0.4≦D≦4.0, 0.4≦D≦3.0, 0.4≦D≦2.0, 0.4≦D≦1.5, 0.4≦D≦1.2, 0.4≦D≦0.8, or 0.4≦D≦0.6.
[0070] When the ratio of the nitrogen element to the transition metal element content is within an appropriate range, the hard carbon material can better combine high reversible capacity per gram with good electronic conductivity and rapid charge / discharge characteristics. In some embodiments, C and D satisfy 3.0≦C / D≦18. For example, C / D is about 3.0, about 3.5, about 4.0, about 4.5, about 5.0, about 5.5, about 6.0, about 6.5, about 7.0, about 7.5, about 8.0, about 8.5, about 9.0, about 9.5, about 10.0, about 10.5, about 11.0, about 11.5, about 12.0, about 12.5, about 13.0, about 13.5, about 14, about 15, about 16, about 17, or about 18, or within a range consisting of any two of these values. Optionally, C and D satisfy 4.0≦C / D≦18, 5.0≦C / D≦18, 6.0≦C / D≦18, 6.5≦C / D≦18, 7.0≦C / D≦18, 7.5≦C / D≦18, 8.0≦C / D≦18, 8.5≦C / D≦18, 9.0≦C / D≦18, or 10.0≦C / D≦18.
[0071] The transition metal element has an empty orbital and can be complexed with the lone pair of the nitrogen element. The present invention is not particularly limited to the type of the transition metal element, and in some embodiments, the transition metal element includes, but is not limited to, at least one of Mn, Co, Ni, Cu, Zn, Sc, Ti, V, Cr, Fe, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, W, Pt, and Au. Optionally, the transition metal element includes at least one of Mn, Co, Ni, Cu, and Zn.
[0072] In some embodiments, the volume particle size Dv50 of the transition metal particles in the negative electrode active material is 10 nm to 100 nm. The volume particle size of the transition metal particles in the negative electrode active material can be measured using a transmission electron microscope (TEM), and an exemplary measurement method includes the following steps. Using a transmission electron microscope (TEM), a 200 nm x 200 nm area of the hard carbon material is scanned in dark field imaging mode to obtain a TEM image, where the highlighted particles indicate transition metal particles. The average value of the longest and shortest diagonal lengths of the highlighted particles is taken as the volume particle size of the transition metal particles, and the average value of multiple measurements at different positions is taken as Dv50.
[0073] In some embodiments, the nitrogen element and the transition metal element are uniformly distributed in the hard carbon material. For example, when the average content of the nitrogen element in any 500 nm × 500 nm area on the surface of the hard carbon material is M1, and the average content of the nitrogen element in any 500 nm × 500 nm area inside the hard carbon material is M2, M1 and M2 satisfy 0.9 ≦ M2 / M1 ≦ 1.1. When the average content of the transition metal element in any 500 nm × 500 nm area on the surface of the hard carbon material is M3, and the average content of the transition metal element in any 500 nm × 500 nm area inside the hard carbon material is M4, M3 and M4 satisfy 0.9 ≦ M4 / M3 ≦ 1.1.
[0074] Of course, the hard carbon material of the present invention can further contain elements other than the above carbon element, hydrogen element, nitrogen element and transition metal element, such as oxygen element.
[0075] In some embodiments, the negative electrode active material further includes a conductive carbon shell layer located on the surface of the hard carbon material. By coating the surface of the hard carbon material with a conductive carbon shell layer, the interface stability of the negative electrode active material can be improved, and thus the initial coulombic efficiency of the negative electrode active material can be improved. In addition, by coating the surface of the hard carbon material with a conductive carbon shell layer, the storage sites of the negative electrode active material can be increased, and the negative electrode active material can have a higher reversible capacity per gram. The present invention is not particularly limited to the type of the conductive carbon shell layer, and can be selected according to actual requirements. As an example, the conductive carbon shell layer includes at least one of amorphous carbon, graphene, carbon nanotubes, and vapor-grown carbon, but is not limited thereto.
[0076] In some embodiments, the negative electrode active material has a volume particle size Dv50 of 3 μm to 15 μm. Optionally, the negative electrode active material has a volume particle size Dv50 of 3 μm to 14 μm, 3 μm to 12 μm, 3 μm to 10 μm, 3 μm to 8 μm, 4 μm to 14 μm, 4 μm to 12 μm, 4 μm to 10 μm, 4 μm to 8 μm, 5 μm to 14 μm, 5 μm to 12 μm, 5 μm to 10 μm, or 5 μm to 8 μm.
[0077] In some embodiments, the negative electrode active material has a volume particle size Dv99 of 10 μm to 45 μm. Optionally, the negative electrode active material has a volume particle size Dv99 of 10 μm to 40 μm, 10 μm to 36 μm, 10 μm to 32 μm, 10 μm to 28 μm, 10 μm to 24 μm, 10 μm to 20 μm, 12 μm to 40 μm, 12 μm to 36 μm, 12 μm to 32 μm, 12 μm to 28 μm, 12 μm to 24 μm, 12 μm to 20 μm, 15 μm to 40 μm, 15 μm to 36 μm, 15 μm to 32 μm, 15 μm to 28 μm, 15 μm to 24 μm, or 15 μm to 20 μm.
[0078] The negative electrode active material of the present invention can have a high initial reversible capacity per gram. In some embodiments, the initial reversible capacity per gram of the negative electrode active material at 0V to 2.0V is 300mAh / g to 1000mAh / g, and optionally 350mAh / g to 1000mAh / g, 380mAh / g to 1000mAh / g, 400mAh / g to 1000mAh / g, 420mAh / g to 1000mAh / g, 450mAh / g to 1000mAh / g, 480mAh / g to 1000mAh / g, or 500mAh / g to 1000mAh / g.
[0079] The initial reversible capacity per gram of the negative electrode active material at 0V to 2.0V can be obtained by the following measurement method. A piece of negative electrode coated on one side is taken, cut into a certain area to be used as a working electrode, and then a lithium sheet (or sodium sheet, etc.) is used as a counter electrode, a porous polyethylene film is used as a separator, and an electrolyte is injected and assembled to obtain a button battery. The button battery is discharged to 0V at three small currents of 0.05C / 50μA / 20μA, respectively, and then charged at a constant current of 0.1C to 2.0V, and the initial charge capacity of the button battery is recorded. The initial reversible capacity per gram of the negative electrode active material at 0V to 2.0V = initial charge capacity of the button battery / mass of the negative electrode active material. The specific components of the electrolyte are not particularly limited, but for example, the electrolyte can be a LiPF6 solution with a concentration of 1 mol / L, and the solvent can be obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a mass ratio of 1:1.
[0080] In the present invention, the content of each element in the negative electrode active material is measured by devices and methods known in the art, such as an elemental analyzer, X-ray photoelectron spectroscopy (XPS) analysis technique, X-ray fluorescence spectroscopy (XRF) analysis technique, inductively coupled plasma atomic emission spectroscopy (ICP-AES) analysis technique, inductively coupled plasma mass spectrometry (ICP-MS) analysis technique, atomic emission spectroscopy (AES) analysis technique, and atomic absorption spectroscopy (AAS) analysis technique. In the present invention, both the particle diameters Dv50 and Dv99 of the material have meanings known in the art. They respectively indicate the particle diameters corresponding to when the cumulative volume distribution percentage of the material reaches 50% and 99%, and can be measured by equipment and methods known in the art. For example, they can be measured with reference to GB / T 19077-2016 Laser Diffraction Method for Particle Size Distribution. An exemplary measurement method includes the following steps. Weigh 1 g of the sample, uniformly mix it with 20 mL of deionized water and a small amount of dispersant, perform ultrasonic treatment on it with an ultrasonic device for 5 minutes, then inject the solution into the sample injection system Hydro 2000SM for measurement. For example, the measuring device uses Mastersizer 3000 manufactured by Malvern. During the measurement, when the laser beam passes through the dispersed particle sample, the particle size of the particles is measured by measuring the intensity of the scattered light, and then the particle size distribution of the particles in this scattered spectrum is calculated. To ensure the accuracy of the measurement results, each sample is measured more than 3 times, and the average value of the obtained measurement results is taken as the final measurement result. Preparation method
[0081] The second aspect of the present invention provides a method for preparing a negative electrode active material, and the preparation method includes the following steps. Step S10: Provide a hard carbon precursor, a nitrogen source, and a transition metal source. Step S20: Uniformly mix the above hard carbon precursor, the above nitrogen source, and the above transition metal source to obtain an initial raw material. Step S30: Pre-oxidize the initial raw material obtained in S20 at a first temperature T1 to obtain a first intermediate product, where T1 satisfies T1≤300°C. Step S40: Perform a primary sintering treatment on the first intermediate product obtained in S30 at a second temperature T2 to obtain a hard carbon material, where T2 satisfies 600°C≤T2≤1000°C. Here, the above hard carbon material contains a carbon element, a hydrogen element, a nitrogen element, and a transition metal element. When the mass percentage of the above carbon element is A%, the mass percentage of the above hydrogen element is B%, the mass percentage of the above nitrogen element is C%, and the mass percentage of the above transition metal element is D% with respect to the total mass of the above hard carbon material, A and B satisfy 0.003≤B / A≤0.050, C satisfies 0<C≤12.0, and D satisfies 0<D≤5.0.
[0082] The preparation method according to the second aspect of the present invention can prepare the negative electrode active material according to any of the examples of the first aspect of the present invention.
[0083] In the prior art, small molecular amine is generally used as nitrogen source, and during sintering, small molecular amine is easily volatilized, so that the doping amount and doping efficiency of nitrogen element are low. In the preparation method provided by the present invention, a transition metal source is added, and the vacant orbital of the transition metal element can be complexed with the lone pair of nitrogen element, so that the volatilization of the nitrogen source can be reduced, and the doping amount and doping efficiency of the nitrogen element can be increased, and the polymerization of hard carbon precursor can be promoted by adding a transition metal source.
[0084] In addition, in the preparation method provided by the present invention, the nitrogen element and the transition metal element are introduced into the hard carbon precursor, which can ensure that the obtained hard carbon material has uniformly doped nitrogen element and transition metal element.
[0085] In the present invention, the types of the hard carbon precursor, the nitrogen source, and the transition metal source are not particularly limited, and can be selected according to actual requirements.
[0086] In the present invention, the amounts of the hard carbon precursor, the nitrogen source, and the transition metal source are not particularly limited and can be selected according to actual requirements. For example, the mass ratio of the nitrogen source to the hard carbon precursor is 5:100 to 60:100, and the mass ratio of the transition metal source to the hard carbon precursor is 1:100 to 20:100.
[0087] In some embodiments, the hard carbon precursor may include at least one of a polymer, a pitch, and a biomass material. For example, the polymer may include at least one of an epoxy resin, a phenolic resin, a polyfurfuryl alcohol, a polyvinyl alcohol, and a polythiophene. For example, the biomass material may include at least one of glucose, fructose, sucrose, maltose, starch, and cellulose. The biomass material may be directly available commercially or may be extracted from materials such as wood, fruit shells, etc.
[0088] In some embodiments, the nitrogen source may include an organic amine containing 1 to 20 carbon atoms and its salt (e.g., a quaternary ammonium salt). The organic amine may include, but is not limited to, an aliphatic amine, an alcohol amine, an amide, an alicyclic amine, an aromatic amine, a naphthylamine, and the like. As an example, the nitrogen source may include at least one of melamine, hexadecyltrimethylammonium bromide, dicyandiamide, o-phenylenediamine, m-phenylenediamine, p-phenylenediamine, phenyleneamine, ethylenediamine, hexanediamine, hexamethylenetetramine, triethylenetetramine, and tetraethylenepentamine.
[0089] In some embodiments, the transition metal source may include at least one of an oxide, a halide, a hydroxide, a sulfate, a carbonate, an oxalate, a nitrate, and an acetate of a transition metal element. Optionally, the transition metal source may be dissolved in water.
[0090] In the present invention, the hard carbon precursor, the nitrogen source, and the transition metal source may be mixed in any manner, for example, by polymerization mixing, reduced graphene oxide (RGO)-assisted polymerization mixing, carbon nanotube (CNT)-assisted polymerization mixing, dissolution mixing, vibration mixing, ball mill mixing, shear mixing, etc.
[0091] Polymerization mixing refers to uniformly mixing each component by polymerizing the components at a certain temperature (e.g., 100°C to 120°C). In particular, when the hard carbon precursor is a biomass material, this mixing method can be used. At this time, the hydroxyl group in the biomass material and the amino group in the nitrogen source can undergo a condensation polymerization reaction using a transition metal element as a catalyst.
[0092] RGO-assisted polymerization mixing and CNT-assisted polymerization mixing refer to adding RGO or CNT solution to uniformly mix each component during polymerization reaction.
[0093] The term "dissolving and mixing" refers to dissolving each component in a solvent (such as water) and then evaporating and drying the components so as to uniformly mix them.
[0094] Vibration mixing refers to mixing each component uniformly under vibration conditions. Ball mill mixing refers to mixing each component uniformly by the impact and milling action of ball beads (for example, zirconium oxide ball mill beads). The term "shear mixing" refers to mixing each component uniformly by applying shear force using a shearing machine or a crusher having a stirring paddle or a stirring blade.
[0095] In the preparation method of the present invention, the micro-oxidation treatment is favorable to increasing the pore structure and the number of oxygen-containing functional groups (e.g., hydroxyl groups, carbonyl groups, etc.) of the hard carbon material, and is also favorable to improving the crosslinking degree of the hard carbon precursor, the porosity of the hard carbon material, and the carbon yield.
[0096] In some embodiments, the pre-oxidation atmosphere may be a slightly oxidizing atmosphere, optionally an air atmosphere. A slightly oxidizing atmosphere refers to a protective gas having a slight or weak oxidizing capacity, which is generally considered to be no greater than that of air.
[0097] In some embodiments, T1 satisfies 140°C≦T1≦300°C, 140°C≦T1≦280°C, 140°C≦T1≦260°C, 140°C≦T1≦240°C, 140°C≦T1≦220°C, 140°C≦T1≦200°C, 150°C≦T1≦300°C, 150°C≦T1≦280°C, 150°C≦T1≦260°C, 150°C≦T1≦240°C, 150°C≦T1≦220°C, or 150°C≦T1≦200°C.
[0098] In some embodiments, the duration of the pre-oxidation treatment may be 2 hours to 48 hours, but the present invention is not limited thereto.
[0099] In some embodiments, the primary sintering atmosphere may be an inert atmosphere, such as a nitrogen atmosphere, an argon atmosphere, a helium atmosphere, or a mixture of any two or more thereof.
[0100] In some embodiments, T2 satisfies 600°C≦T2≦1000°C, 650°C≦T2≦1000°C, 700°C≦T2≦1000°C, 600°C≦T2≦980°C, 650°C≦T2≦980°C, 700°C≦T2≦980°C, 600°C≦T2≦950°C, 650°C≦T2≦950°C, 700°C≦T2≦950°C, 600°C≦T2≦900°C, 650°C≦T2≦900°C, 700°C≦T2≦900°C, 600°C≦T2≦850°C, 650°C≦T2≦850°C, or 700°C≦T2≦850°C. In some embodiments, the time for the primary sintering process may be 1 h to 10 h, but the present invention is not limited thereto.
[0101] In some embodiments, the preparation method may further include the following steps: Step S50: The hard carbon material obtained in S40 is uniformly mixed with the conductive carbon precursor, and then subjected to secondary sintering treatment at a third temperature T3 to obtain a hard carbon material having a conductive carbon shell layer on its surface, where T3 satisfies T3≦1000°C.
[0102] The present invention does not have any particular limitations on the type of the conductive carbon precursor, and can be selected according to actual requirements. In some embodiments, the conductive carbon precursor may include at least one of graphene, carbon nanotubes, vapor-grown carbon fibers, acetylene, polymers, and pitch. As an example, the polymer may include at least one of epoxy resin, phenolic resin, polyfurfuryl alcohol, polyvinyl alcohol, and polythiophene.
[0103] In some embodiments, the secondary sintering atmosphere can be an inert atmosphere, for example, a nitrogen atmosphere, an argon atmosphere, a helium atmosphere, or a mixture of any two or more thereof.
[0104] In some embodiments, T3 satisfies 700°C < T3 < 1000°C, 750°C < T3 < 1000°C, 800°C < T3 < 1000°C, 850°C < T3 < 1000°C, or 900°C < T3 < 1000°C.
[0105] In some embodiments, the time for the secondary sintering process may be 1 h to 10 h, but the present invention is not limited thereto. negative electrode piece
[0106] A third aspect of the present invention provides a negative electrode piece comprising a negative electrode current collector and a negative electrode film layer, the negative electrode film layer comprising the negative electrode active material of the first aspect of the present invention or the negative electrode active material obtained by the preparation method of the second aspect of the present invention.
[0107] The negative electrode piece of the present invention can improve the rapid charge / discharge characteristics and cycle characteristics of the electrochemical device, and can also increase the output voltage and energy density of the entire electrochemical device.
[0108] In the negative electrode piece of the present invention, the negative electrode film layer can be provided on one surface or both surfaces of the negative electrode current collector. The negative electrode film layer does not exclude other negative electrode active materials other than the negative electrode active material of the first aspect of the present invention. The specific type of the other negative electrode active material is not specifically limited and can be selected as needed. As an example, the other negative electrode active material can be graphite, mesocarbon microbeads (MCMB), soft carbon, and Li4Ti5O 12 may include, but is not limited to, at least one of the following:
[0109] The negative electrode film layer may optionally include a conductive agent. The specific type of the conductive agent is not specifically limited and can be selected as needed. For example, the conductive agent includes at least one of conductive graphite, carbon black, acetylene black, ketjen black, carbon nanotube, graphene, and carbon nanofiber, but is not limited thereto.
[0110] The negative electrode film layer may optionally include an adhesive. The specific type of the adhesive is not specifically limited and can be selected as needed. As an example, the adhesive includes at least one of styrene butadiene rubber (SBR), sodium alginate, carboxymethyl cellulose, hydroxypropyl cellulose, polyvinyl alcohol, polyvinylpyrrolidone, polyurethane, and epoxy resin, but is not limited thereto.
[0111] The negative electrode film layer may optionally include a thickener. The specific type of the thickener is not specifically limited and can be selected as needed. As an example, the thickener includes, but is not limited to, sodium carboxymethylcellulose (CMC-Na).
[0112] The negative electrode current collector may be a metal foil or a porous metal plate, for example, a foil or a porous plate of a metal such as copper, nickel, titanium, iron, aluminum, or an alloy thereof. As an example, the negative electrode current collector may be a copper foil (for example, used in a lithium secondary battery system) or an aluminum foil (for example, used in a sodium secondary battery system).
[0113] The negative electrode piece of the present invention can be prepared according to a conventional method in the art. Usually, the negative electrode active material and optional conductive agent, adhesive, thickener, etc. are dispersed in a solvent to form a uniform negative electrode slurry, and then the negative electrode slurry is applied to a negative electrode current collector, and the negative electrode piece is obtained through processes such as drying and cold rolling. The solvent can be N-methylpyrrolidone (NMP) or deionized water. Electrochemical Equipment
[0114] A fourth aspect of the present invention provides an electrochemical device, which includes any device in which an electrochemical reaction occurs to convert chemical energy into electrical energy or vice versa, examples of which may include, for example, any lithium secondary battery or sodium secondary battery. In particular, lithium secondary batteries include lithium ion secondary batteries, lithium polymer secondary batteries or lithium ion polymer secondary batteries, and sodium secondary batteries include sodium ion secondary batteries.
[0115] The negative electrode pieces used in the electrochemical device of the present invention are the negative electrode pieces according to the third aspect of the present invention, so that the electrochemical device of the present invention can have both high energy density, good cycle characteristics, and rapid charge / discharge characteristics. In some embodiments, the electrochemical device of the present invention further comprises a positive electrode piece, a separator, and an electrolyte.
[0116] In some embodiments, the positive electrode pieces, the negative electrode pieces, and the separator can be prepared into an electrode assembly by a winding process or a stacking process.
[0117] The electrochemical device of the present invention further includes an exterior body used to package the electrode assembly and the electrolyte. In some embodiments, the exterior body may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc., or a soft packing, such as a bag-shaped soft packing. The material of the soft packing may be at least one of plastic, such as an aluminum plastic film, polypropylene, polybutylene terephthalate, and polybutylene succinate. [Positive electrode piece]
[0118] The materials, construction and method of manufacture of the positive electrode pieces used in the electrochemical devices of the present invention may include any technique known in the art.
[0119] In some embodiments, the positive electrode piece includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector. The positive electrode film layer typically includes a positive electrode active material and optional conductive and adhesive agents.
[0120] In some embodiments, the positive electrode current collector may be a metal foil or a porous metal plate, for example, a foil or a porous plate of a metal such as aluminum, copper, nickel, titanium, silver, or an alloy thereof. As an example, the positive electrode current collector may be an aluminum foil.
[0121] When used in a lithium secondary battery, the positive electrode active material may include a material capable of absorbing and releasing lithium, and the specific type is not specifically limited and can be selected as necessary. As an example, the positive electrode active material used in the lithium secondary battery includes at least one of lithium cobalt oxide, lithium nickel cobalt manganese ternary material, lithium nickel cobalt aluminum ternary material, lithium iron phosphate, lithium rich manganese material, and modified compounds thereof, but is not limited thereto. The modified compound of each of the positive electrode active materials may be modified by doping the positive electrode active material, may be modified by coating the surface of the positive electrode active material, or may be modified by doping and coating the surface of the positive electrode active material.
[0122] When used in a sodium secondary battery, the positive electrode active material may include a material capable of absorbing and releasing lithium, and the specific type is not specifically limited and can be selected as necessary. As an example, the positive electrode active material used in the sodium secondary battery includes at least one of sodium copper iron manganese oxide, Prussian blue material, Prussian white material, sodium-containing polyanion compound, and modified compounds thereof, but is not limited thereto. The modified compound of each of the positive electrode active materials may be modified by doping the positive electrode active material, may be modified by coating the surface of the positive electrode active material, or may be modified by doping and coating the positive electrode active material.
[0123] The specific type of the conductive agent is not specifically limited and can be selected as necessary. For example, the conductive agent includes at least one of conductive graphite, carbon black, acetylene black, ketjen black, carbon nanotube, graphene, and carbon nanofiber, but is not limited thereto.
[0124] The specific type of the adhesive is not specifically limited and can be selected according to need.As an example, the adhesive includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene ternary copolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene ternary copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinyl alcohol, but is not limited thereto.
[0125] The positive electrode pieces can be prepared according to the conventional methods in the art. Usually, the positive electrode active material and any conductive agent, adhesive, etc. are dispersed in a solvent to form a uniform positive electrode slurry, and then the positive electrode slurry is applied to a positive electrode current collector, and the positive electrode pieces are obtained through processes such as drying and cold rolling. The solvent may be N-methylpyrrolidone, but the present invention is not limited thereto. [Electrolyte]
[0126] The electrolyte serves to conduct active ions between the positive and negative electrode pieces. The electrolyte used in the electrochemical device of the present invention may be any electrolyte known in the art.
[0127] In some embodiments, the electrolyte solution includes an organic solvent, an electrolyte salt, and any additives, and the types of the organic solvent, electrolyte salt, and additives are not limited and can be selected as needed.
[0128] In some embodiments, when used in a lithium secondary battery, the electrolyte salt (i.e., lithium salt) may, by way of example only, include at least one of lithium hexafluorophosphate (LiPF), lithium tetrafluoroborate (LiBF), lithium perchlorate (LiClO), lithium hexafluoroarsenate (LiAsF), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluoro(oxalato)borate (LiDFOB), and lithium bis(oxalato)borate (LiBOB).
[0129] When used in a sodium secondary battery, by way of example, the electrolyte salt (i.e., sodium salt) includes at least one of sodium hexafluorophosphate (NaPF6) and sodium perchlorate (NaClO4), but is not limited thereto.
[0130] In some embodiments, by way of example, the organic solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).
[0131] In some embodiments, the additive includes at least one of the following: anode film-forming additive and cathode film-forming additive, but is not limited thereto.As an example, the additive includes at least one of the following: fluoroethylene carbonate (FEC), vinylene carbonate (VC), vinylethylene carbonate (VEC), ethylene sulfate (DTD), propylene sulfate, ethylene sulfite (ES), 1,3-propane sultone (PS), 1,3-propene sultone (PST), cyclic quaternary ammonium salt of sulfonic acid ester, succinic anhydride, succinonitrile (SN), adiponitrile (AND), tris(trimethylsilyl)phosphate (TMSP), and tris(trimethylsilyl)borate (TMSB).
[0132] The electrolyte of the present invention can be prepared according to a conventional method in the art. For example, an organic solvent, an electrolyte salt, and an optional additive can be mixed uniformly to obtain an electrolyte. There is no particular restriction on the order of addition of each material. For example, an electrolyte salt and an optional additive can be added to an organic solvent and mixed uniformly to obtain an electrolyte, or an electrolyte salt can be first added to an organic solvent, and then an optional additive can be added to the organic solvent and mixed uniformly to obtain an electrolyte. [Separator]
[0133] The separator is provided between the positive and negative electrode pieces, and serves mainly to prevent short circuit between the positive and negative electrodes while allowing active ions to pass through. The present invention is not particularly limited in the type of separator, and any known separator having a porous structure with good chemical and mechanical stability may be used. The separator may be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different. In some embodiments, the separator comprises a material, such as a polymer or inorganic material, that is stable with the electrolyte of the present invention.
[0134] For example, the separator may include a substrate layer and an optional surface treatment layer. The substrate layer is a nonwoven fabric, film or composite film having a porous structure, and the material of the substrate layer includes at least one of polyethylene, polypropylene, polyethylene terephthalate, and polyimide. As an example, polypropylene porous film, polyethylene porous film, polypropylene nonwoven fabric, polyethylene nonwoven fabric, polypropylene-polyethylene-polypropylene porous composite film, glass fiber separator, porous filter paper, etc. can be adopted.
[0135] A surface treatment layer may or may not be provided on the surface of the base layer. In some embodiments, a surface treatment layer is provided on at least one surface of the base layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer formed by mixing a polymer and an inorganic material.
[0136] The inorganic layer includes inorganic particles and an adhesive, and the inorganic particles include at least one of alumina, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The adhesive includes at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.
[0137] The polymer layer includes a polymer, the polymeric material including at least one of polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene ether, polyvinylidene fluoride, and vinylidene fluoride-hexafluoropropylene copolymer. electronic equipment
[0138] A fourth aspect of the invention provides an electronic device comprising an electrochemical device according to the third aspect of the invention. The electronic device of the present invention is not particularly limited and may be any known electronic device used in the prior art. In some embodiments, the electronic device may include, but is not limited to, a notebook computer, a pen-input computer, a mobile computer, an electronic book player, a mobile phone, a mobile fax machine, a portable copy machine, a mobile printer, a headphone stereo, a video recorder, a liquid crystal television, a handy cleaner, a portable CD player, a mini disc, a transceiver, an electronic notebook, a calculator, a memory card, a portable tape recorder, a radio, a backup power source, a motor, an automobile, a motorcycle, an assisted bicycle, a bicycle, a lighting device, a toy, a game machine, a clock, an electric tool, a flashlight, a camera, a large-scale storage battery for home use, and a lithium-ion capacitor. EXAMPLES
[0139] The following examples are provided to more specifically describe the contents of the present disclosure, and these examples are merely illustrative, and it will be apparent to those skilled in the art that various modifications and variations can be made within the scope of the contents of the present disclosure.Unless otherwise specified, all parts, percentages, and ratios reported in the following examples are calculated by weight, and all reagents used in the examples are commercially available or obtained by synthesis according to conventional methods, and can be used directly without further treatment, and all equipment used in the examples are commercially available. Measurement method
[0140] (1) Measurement of the initial reversible capacity per gram and initial coulombic efficiency of the negative electrode active material A negative electrode piece with one side coated was taken and cut into a wafer with a diameter of 14 mm to be used as the working electrode, then a lithium sheet with a diameter of 18 mm was used as the counter electrode, a porous polyethylene film with a diameter of 20 mm was used as the separator, and the electrolyte was injected and assembled to obtain a button battery. The button battery was discharged to 0 V at three small current levels of 0.05 C / 50 μA / 20 μA, and the initial discharge capacity of the button battery was recorded. After leaving it for 10 minutes, the button battery was charged at a constant current of 0.1 C to 2.0 V, and the initial charge capacity of the button battery was recorded.
[0141] [Formula 1] Initial reversible capacity per gram of negative active material (mAh / g) = Initial charging capacity of button battery / Mass of negative active material [Formula 2] Initial coulombic efficiency of negative electrode active material = (initial charge capacity of button battery / initial discharge capacity of button battery) x 100% (2) Measurement of the rapid charging characteristics of lithium-ion secondary batteries
[0142] In an environment of 25°C, the lithium-ion secondary battery was charged at a constant current of 2C to 4.48V, and the charge capacity obtained at this stage was designated as Q1. Thereafter, the lithium-ion secondary battery was charged at a constant voltage of 4.48V to a current of less than 0.05C, and the charge capacity at this stage was designated as Q2. After leaving the battery to stand for 10 minutes, the lithium-ion secondary battery was discharged at a constant current of 0.5C to 2.0V.
[0143] Q1+Q2 indicates the total charging capacity of a lithium-ion secondary battery at 2C, and the present invention uses Q1 / (Q1+Q2) to characterize the fast charging characteristics of a lithium-ion secondary battery; the higher the value of this ratio, the better the fast charging characteristics of the lithium-ion secondary battery. (3) Measurement of cycle characteristics of lithium-ion secondary batteries
[0144] In an environment of 12°C, the lithium-ion secondary battery was charged at a constant current of 0.7C to 4.48V, then charged at a constant voltage of less than 0.05C, and allowed to stand for 10 minutes, after which the lithium-ion secondary battery was discharged at a constant current of 1C to 2.0V, which constitutes one cycle of charge-discharge process, and the discharge capacity at this time was the discharge capacity of the first cycle. The lithium-ion secondary battery was subjected to 500 charge-discharge cycles using the above method, and the discharge capacity of the 500th cycle was recorded. [Formula 3] Capacity retention rate of lithium-ion secondary battery after 500 cycles = (discharge capacity at 500th cycle / discharge capacity at first cycle) x 100% When each of the above measurements was performed, five samples were measured for each Example and Comparative Example, and the average value of the obtained measurement results was regarded as the final measurement result. Example 1 Preparation of negative electrode active material
[0145] 100 parts by mass of glucose (hard carbon precursor), 15 parts by mass of melamine (nitrogen source), and 2 parts by mass of cobalt sulfate (transition metal source) were mixed in this ratio, and then polymerized in deionized water at 100°C to 120°C for 12 hours. Thereafter, the mixture was subjected to a slight oxidation treatment in an air atmosphere at 180°C for 10 hours, and then primarily sintered in an atmosphere furnace in a nitrogen atmosphere at 700°C for 2 hours, after which it was classified and crushed to obtain a negative electrode active material. Using an elemental analyzer (Elementar UNICUBE, Germany) and X-ray photoelectron spectroscopy (XPS) analysis technology, the mass percentages of carbon, hydrogen, nitrogen and transition metal elements in the above negative electrode active material were measured, and the measurement results were shown in Table 2 as A%, B%, C% and D%, respectively. Preparation of negative electrode pieces
[0146] The negative electrode active material, styrene butadiene rubber (SBR) as an adhesive, and sodium carboxymethylcellulose (CMC-Na) as a thickener were mixed in a mass ratio of 97:2:1 with sufficient stirring in an appropriate amount of deionized water as a solvent to prepare a negative electrode slurry with a solid content of 40%. The negative electrode slurry was applied to a copper foil as a negative electrode current collector, dried at 85°C, cold-rolled, cut, slit, and vacuum-dried at 120°C for 12 hours to obtain negative electrode pieces. Preparation of positive electrode pieces
[0147] The positive electrode active material LiCoO2, the conductive agent carbon black (Super P), and the adhesive PVDF were mixed in a mass ratio of 97:1.4:1.6 with sufficient stirring in an appropriate amount of NMP as a solvent to prepare a positive electrode slurry with a solid content of 72%. The positive electrode slurry was applied to an aluminum foil as a positive electrode current collector, dried at 85°C, and then cold-rolled, cut, and slit. The resulting product was then vacuum-dried at 85°C for 4 hours to obtain positive electrode pieces. Preparation of electrolyte
[0148] In a glove box with a dry argon atmosphere, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a mass ratio of 30:50:20 to obtain an organic solvent, and 1,3-propane sultone, fluoroethylene carbonate, and LiPF6 were added to the organic solvent and mixed uniformly to obtain an electrolyte solution. Here, the concentration of LiPF6 was 1 mol / L, and the mass percentage of 1,3-propane sultone was 1.5% and the mass percentage of fluoroethylene carbonate was 2% relative to the total mass of the electrolyte solution. Preparation of the separator
[0149] As the separator, a porous polyethylene film with a thickness of 7 μm was used. Preparation of lithium-ion secondary batteries
[0150] The positive electrode piece, separator, and negative electrode piece were stacked and wound in this order to obtain an electrode assembly. The electrode assembly was then placed in an aluminum plastic film exterior body, and the above-mentioned electrolyte solution was injected. After undergoing processes such as vacuum packaging, standing, chemical formation, shaping, and capacity measurement, a lithium ion secondary battery was obtained. Examples 2 to 8
[0151] The preparation method of the lithium ion secondary battery was similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. The specific parameters are shown in Table 1. Comparative Example 1
[0152] The preparation method of the lithium ion secondary battery was similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. 100 parts by mass of glucose was subjected to slight oxidation treatment in an air atmosphere at 180° C. for 10 hours, and then sintered in a nitrogen atmosphere in an atmospheric furnace at 700° C. for 2 hours, and then classified and crushed to obtain a negative electrode active material. Comparative Example 2
[0153] The preparation method of the lithium ion secondary battery was similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. 100 parts by mass of glucose was subjected to slight oxidation treatment in an air atmosphere at 180° C. for 10 hours, and then sintered in a nitrogen atmosphere in an atmospheric furnace at 850° C. for 2 hours, and then classified and crushed to obtain a negative electrode active material. Comparative Example 3
[0154] The preparation method of the lithium ion secondary battery was similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. 100 parts by mass of glucose was subjected to slight oxidation treatment in an air atmosphere at 180° C. for 10 hours, and then sintered in a nitrogen atmosphere in an atmospheric furnace at 1000° C. for 2 hours, and then classified and crushed to obtain a negative electrode active material. Comparative Example 4
[0155] The preparation method of the lithium ion secondary battery was similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. 100 parts by mass of glucose (hard carbon precursor) and 15 parts by mass of melamine (nitrogen source) were mixed in this ratio, and then subjected to a slight oxidation treatment in an air atmosphere at 180°C for 10 hours. Thereafter, the mixture was sintered in a nitrogen atmosphere in an atmospheric furnace at 850°C for 2 hours, and then classified and crushed to obtain a negative electrode active material. Comparative Example 5
[0156] The preparation method of the lithium ion secondary battery was similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. 100 parts by mass of glucose (hard carbon precursor), 15 parts by mass of melamine (nitrogen source), and 2 parts by mass of reduced graphene oxide (RGO) were mixed in this ratio, and then subjected to a slight oxidation treatment in an air atmosphere at 180°C for 10 hours. Thereafter, the mixture was sintered in an atmosphere furnace in a nitrogen atmosphere at 850°C for 2 hours, and then classified and crushed to obtain a negative electrode active material. [Table 1] [Table 2] [Table 3]
[0157] Table 2 shows the measurement results of Examples 1 to 8, and Table 3 shows the measurement results of Comparative Examples 1 to 5.
[0158] As can be seen from the measurement results of Comparative Examples 1 to 3, as the primary sintering temperature increases, the initial reversible capacity per gram of the negative electrode active material decreases, but the rapid charging characteristics of the lithium ion secondary battery improve slightly. As can be seen from the measurement results of Comparative Examples 2, 4, and 5, when the negative electrode active material is doped with only nitrogen element, the effect of improving the initial reversible capacity per gram of the negative electrode active material and the rapid charging characteristics of the lithium ion secondary battery is limited.
[0159] As can be seen from the measurement results of Examples 1 to 8 and Comparative Examples 1 to 5, by simultaneously doping the negative electrode active material with appropriate amounts of nitrogen element and transition metal element, the initial reversible capacity per gram of the negative electrode active material and the rapid charging characteristics of the lithium ion secondary battery were both significantly increased.
[0160] Furthermore, as can be seen from the measurement results of Examples 1 to 8, when the mass of the transition metal source is the same, the content of the nitrogen element doped in the negative electrode active material increases with the increase in the mass of the nitrogen source, and the rapid charging characteristics of the lithium ion secondary battery also increase accordingly. The reason is that the negative electrode active material prepared in Examples 1 to 8 is a low-temperature hard carbon material, and its hydrogen element content is generally high, so that the electronic conductivity and rapid charging and discharging characteristics of the negative electrode active material are deteriorated, but by doping an appropriate amount of nitrogen element and transition metal element therein, these elements function as good carriers of electrons, improving the electronic conductivity of the negative electrode active material, and when the nitrogen element is present on the graphite crystallite end face, it can reduce the band gap energy, thereby changing the electronic structure of the entire negative electrode active material, further improving its electronic conductivity, and further improving the rapid charging characteristics of the lithium ion secondary battery.
[0161] Next, the applicant further investigated the influence of the type of carbonaceous precursor and nitrogen source on the characteristics of lithium ion secondary batteries.
[0162] The preparation methods of the lithium ion secondary batteries of Examples 9 to 12 and Comparative Examples 6 to 7 are similar to those of Example 1 except that the preparation parameters of the negative electrode active material are different, and are specifically shown in Table 4, where CTAB stands for hexadecyltrimethylammonium bromide. Table 5 shows the measurement results of Examples 9 to 12 and Comparative Examples 6 to 7. [Table 4] [Table 5]
[0163] As can be seen from the measurement results of Comparative Example 4 and Comparative Example 5 in Table 3, in the preparation process of the negative electrode active material, the added nitrogen source such as melamine is easily volatilized during sintering, which is disadvantageous for introducing nitrogen element into the negative electrode active material, and the mass percentages of nitrogen element in the negative electrode active materials prepared in Comparative Example 4 and Comparative Example 5 were 1.2% and 1.8%, respectively. On the other hand, in the preparation method of the negative electrode active material of the present invention, the nitrogen source and the transition metal source are added simultaneously, so that the vacant orbital of the transition metal element can be complexed with the lone electron pair of the nitrogen element, thereby reducing the volatilization of the nitrogen source and increasing the doping amount and doping efficiency of the nitrogen element in the negative electrode active material.
[0164] Furthermore, as can be seen from the measurement results of Examples 9 to 12 and Comparative Examples 6 to 7, when the negative electrode active material is doped with only a transition metal element, the effect of improving the initial reversible capacity per gram of the negative electrode active material and the rapid charging characteristics of the lithium ion secondary battery is limited.
[0165] As can be seen from the measurement results of Examples 4 to 5 and Examples 9 to 12, since the types of carbonaceous precursor and nitrogen source are different, there are slight differences in the content of nitrogen element doped in the negative electrode active material, the initial reversible capacity per gram of the negative electrode active material, and the fast charging characteristics of the lithium ion secondary battery.
[0166] Next, the applicant further examined the effect of the mass of the transition metal source on the content of the nitrogen element doped in the negative electrode active material. The preparation methods of the lithium ion secondary batteries of Examples 13 to 15 were similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. [Table 6]
[0167] As can be seen from Table 6, with the increase in the mass of the transition metal source, the content of the nitrogen element doped in the negative active material also increases, but the content of the nitrogen element does not continue to increase.
[0168] Next, the applicant further investigated the effect of the type of transition metal source on the content of nitrogen element doped in the negative electrode active material.
[0169] The preparation methods of the lithium ion secondary batteries of Examples 16 to 20 were similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. [Table 7]
[0170] As can be seen from Table 7, there is a slight difference in the nitrogen content of the negative electrode active material prepared using different transition metal sources. When the transition metal elements Mn, Co, and Ni are used, the nitrogen content of the negative electrode active material is higher. The reason for this is presumed to be that the transition metal elements Mn, Co, and Ni are easily complexed with the lone electron pair of the nitrogen element to form a coordinate bond.
[0171] Next, the applicant further investigated the change in the plateau voltage of the negative electrode active material at a high potential. The negative electrode pieces prepared in Example 11, Example 14, Example 16, Comparative Example 2 and Comparative Example 8 were assembled into button batteries by the above method, and then the button batteries were charged using a fully automatic constant current constant voltage charger to obtain a series of voltage (V) and capacity per gram (Q) data, which were differentiated with respect to voltage V by capacity per gram Q, and further, a dQ / dV-V curve was drawn with dQ / dV as the ordinate and voltage V as the abscissa, and the specific peak voltage between the voltages of the button batteries of 0.7V to 1.3V, that is, the plateau voltage at high potential, was obtained. The results are shown in Table 8. Comparative Example 8 used commercially available commercial hard carbon. [Table 8]
[0172] Figure 1 shows the results of XPS fitting of the N peak in the negative electrode active material of Example 14. Figure 2 shows the contents of pyrrole nitrogen, pyridine nitrogen, and graphitized nitrogen in the negative electrode active material of Example 14. Figure 3 shows the dQ / dV-V curves of the negative electrode pieces, where curve I shows Comparative Example 8, curve II shows Comparative Example 2, curve III shows Example 14, and curve IV shows Example 16.
[0173] As can be seen from the measurement results in Figures 1 to 3 and Table 8, when the negative electrode active material is doped with nitrogen and a transition metal element, the plateau voltage at high potential decreases, and the entire lithium ion secondary battery can have a higher output voltage and energy density. Next, the applicant further investigated the effects of different methods for preparing negative electrode active materials on the characteristics of lithium ion secondary batteries.
[0174] The preparation method of the lithium ion secondary battery of Examples 21 to 26 was similar to that of Example 1, except that the preparation parameters of the negative electrode active material were different. Specifically, in Examples 21 to 26, 100 parts by mass of glucose (hard carbon precursor), 18 parts by mass of melamine (nitrogen source) and 2 parts by mass of nickel sulfate (transition metal source) were mixed using different mixing methods, and then the mixture was subjected to slight oxidation treatment in an air atmosphere at 180°C for 10 hours, and further subjected to primary sintering in a nitrogen atmosphere in an atmosphere furnace at 850°C for 2 hours, and then classified and crushed to obtain a negative electrode active material. The mixing methods used in Examples 21 to 26 were polymerization mixing, RGO auxiliary polymerization mixing, CNT auxiliary polymerization mixing, ball mill mixing, dissolution mixing and vibration mixing, respectively. Table 9 shows the measurement results of Examples 21 to 26. [Table 9]
[0175] As can be seen from the measurement results in Table 9, the nitrogen element content doped in the negative electrode active material and the fast charging characteristics of the lithium ion secondary battery obtained by different mixing processes under the same raw material conditions are almost the same, although there are slight differences. Next, the applicant further investigated the effect of the conductive carbon shell layer on the characteristics of lithium ion secondary batteries.
[0176] The preparation method of the lithium ion secondary batteries of Examples 27 to 29 was similar to that of Example 14, except that the surface of the hard carbon material was further coated with a conductive carbon shell layer. Specifically, in Examples 27 to 29, the hard carbon material prepared in Example 14 was dispersed in deionized water together with polyacrylonitrile, acetylene, and resorcinol-formaldehyde resin, stirred at room temperature for 10 hours, centrifuged to collect the solid matter, and then subjected to secondary sintering treatment at 900°C for 2 hours in an inert atmosphere to obtain the batteries. Table 10 shows the measurement results of Examples 14, 27 to 29, and Comparative Example 8 (commercially available hard carbon for commercial use was used). [Table 10]
[0177] As can be seen from the measurement results in Table 10, by coating the surface of the hard carbon material with a conductive carbon shell layer, the interface stability of the negative electrode active material can be improved, and the initial coulombic efficiency of the negative electrode active material and the fast charging characteristics and low temperature cycle characteristics of the lithium ion secondary battery can be improved. In addition, by coating the surface of the hard carbon material with a conductive carbon shell layer, the lithium storage sites of the negative electrode active material can be increased, and the negative electrode active material can have a higher initial reversible capacity per gram.
[0178] As described above, the present application is merely a specific embodiment of the present application, and the scope of protection of the present application is not limited thereto, and those skilled in the art can easily think of various equivalent modifications or replacements within the technical scope disclosed in the present application, and all of these modifications or replacements should be included in the scope of protection of the present application. Therefore, the scope of protection of the present application should be based on the scope of the claims.
Claims
1. A negative electrode active material, The negative electrode active material includes a hard carbon material, The hard carbon material contains a carbon element, a hydrogen element, a nitrogen element, and a transition metal element, a mass percentage of the carbon element is A%, a mass percentage of the hydrogen element is B%, a mass percentage of the nitrogen element is C%, and a mass percentage of the transition metal element is D%, relative to a total mass of the hard carbon material, wherein A and B satisfy 0.003≦B / A≦0.050, C satisfies 0<C≦12.0, and D satisfies 0<D≦5.
0.
2. The X-ray photoelectron spectrum of the negative electrode active material contains three different N peaks, namely, nitrogen of pyrrole, nitrogen of pyridine, and nitrogen of graphitization; 2. The negative electrode active material according to claim 1, wherein X is a sum of a peak area corresponding to nitrogen of pyrrole and a peak area corresponding to nitrogen of pyridine, and Y is a peak area corresponding to nitrogen of graphitization, and X and Y satisfy 0.6≦X / Y≦1.
4.
3. The negative electrode active material according to claim 2 , wherein X and Y satisfy 0.7≦X / Y≦1.
3.
4. The hard carbon material is (1) A satisfies 65≦A≦96, (2) B satisfies 0.3≦B≦4.0; (3) C satisfies 0.1≦C≦12.0; (4) D satisfies 0.2≦D≦5.0; (5) A and B satisfy 0.004≦B / A≦0.035; (6) C and D satisfy 3.0≦C / D≦18; (7) The transition metal element includes at least one of Mn, Co, Ni, Cu, Zn, Sc, Ti, V, Cr, Fe, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, W, Pt, and Au; (8) The nitrogen element and the transition metal element are uniformly distributed in the hard carbon material; and (9) The average content of nitrogen elements in any 500 nm × 500 nm area on the surface of the hard carbon material is M 1 The average content of nitrogen element in any 500 nm × 500 nm region in the hard carbon material is M 2 In this case, M 1 and M. 2 0.9≦M 2 / M 1 ≦1.1 is satisfied, (10) The average content of transition metal elements in any 500 nm × 500 nm area on the surface of the hard carbon material is M 3 The average content of transition metal elements in any 500 nm × 500 nm region in the hard carbon material is M 4 In this case, M 3 and M. 4 0.9≦M 4 / M 3 ≦1.1 is satisfied, The negative electrode active material according to claim 1 , which satisfies at least one of the above.
5. The hard carbon material is (1) A satisfies 70≦A≦94, (2) B satisfies 1.0≦B≦2.5; (3) C satisfies 5.0≦C≦12.0; (4) D satisfies 0.2≦D≦1.2; (5) A and B satisfy 0.007≦B / A≦0.030; (6) C and D satisfy 6.5≦C / D≦18, (7) The transition metal element includes at least one of Mn, Co, Ni, Cu, and Zn; The negative electrode active material according to claim 1 , which satisfies at least one of the above.
6. The negative electrode active material of claim 1 , further comprising a conductive carbon shell layer located on a surface of the hard carbon material.
7. 7. The negative electrode active material of claim 6, wherein the conductive carbon shell layer comprises at least one of amorphous carbon, graphene, carbon nanotubes, and vapor-grown carbon.
8. The negative electrode active material is (1) the negative electrode active material has a volume particle diameter Dv50 of 3 μm to 15 μm; (2) the negative electrode active material has a volume particle diameter Dv99 of 10 μm to 45 μm; (3) the volume particle diameter Dv50 of the transition metal particles in the negative electrode active material is 10 nm to 100 nm; (4) The initial reversible capacity per gram of the negative electrode active material at 0 V to 2.0 V is 300 mAh / g to 1000 mAh / g; The negative electrode active material according to any one of claims 1 to 7, which satisfies at least one of the above.
9. Step S10: Providing a hard carbon precursor, a nitrogen source, and a transition metal source; Step S20: uniformly mixing the hard carbon precursor, the nitrogen source, and the transition metal source to obtain an initial raw material; Step S30: Pre-oxidize the initial raw material obtained in S20 at a first temperature T1 to obtain a first intermediate product, where T1 satisfies T1≦300° C.; Step S40: A method for preparing a negative electrode active material, comprising: performing a primary sintering process on the first intermediate product obtained in step S30 at a second temperature T2 to obtain a hard carbon material, where T2 satisfies 600° C.≦T2≦1000° C., The hard carbon material contains a carbon element, a hydrogen element, a nitrogen element, and a transition metal element, a mass percentage of the carbon element is A%, a mass percentage of the hydrogen element is B%, a mass percentage of the nitrogen element is C%, and a mass percentage of the transition metal element is D%, relative to a total mass of the hard carbon material, wherein A and B satisfy 0.003≦B / A≦0.050, C satisfies 0<C≦12.0, and D satisfies 0<D≦5.
0.
10. Step S30 (1) The atmosphere of the preliminary oxidation treatment is a slightly oxidizing atmosphere; (2) T1 satisfies 140°C≦T1≦300°C; (3) The time for the preliminary oxidation treatment is 2 hours to 48 hours; At least one of the following is satisfied: Step S40 (4) The atmosphere for the primary sintering process is an inert atmosphere; (5) T2 satisfies 700°C≦T2≦1000°C; (6) The time for the primary sintering process is 1 h to 10 h; At least one of the following is satisfied: Step S10 (7) The hard carbon precursor includes at least one of a polymer, a pitch, and a biomass material; (8) The nitrogen source comprises an organic amine containing 1 to 20 carbon atoms and a salt thereof; (9) The transition metal source includes at least one of an oxide, a halide, a hydroxide, a sulfate, a carbonate, an oxalate, a nitrate, and an acetate of a transition metal element; At least one of the following is satisfied:
10. The preparation method according to claim 9.
11. 11. The method of claim 9 or 10, further comprising: step S50: uniformly mixing the hard carbon material obtained in S40 with a conductive carbon precursor, and then performing a secondary sintering process at a third temperature T3 to obtain a hard carbon material having a conductive carbon shell layer on its surface, wherein T3 satisfies T3≦1000° C.
12. Step S50 (1) The atmosphere for the secondary sintering treatment is an inert atmosphere; (2) T3 satisfies 700°C≦T3≦1000°C; (3) The time for the secondary sintering process is 1 h to 10 h; (4) The conductive carbon precursor includes at least one of graphene, carbon nanotubes, vapor-grown carbon fibers, acetylene, polymers, and pitch; The preparation method according to claim 11, wherein at least one of the following is satisfied:
13. A negative electrode piece including a negative electrode current collector and a negative electrode film layer, The negative electrode film layer comprises the negative electrode active material according to any one of claims 1 to 8, or the negative electrode active material obtained by the preparation method according to any one of claims 9 to 12.
14. 14. An electrochemical device comprising the anode piece of claim 13.
15. An electronic device comprising the electrochemical device of claim 14.
Citation Information
Patent Citations
Preparation of nitrogen-doped metal carbide material
CN111244465A
High-rate lithium ion battery anode material and preparation method thereof
CN111969210A
Negative electrode composite material and preparation method thereof, negative electrode plate and secondary battery
CN114242966A
Method of manufacturing anode active material, and anode and lithium battery using the anode active material
US20130280603A1